Quantifying the causes and consequences of variation in satellite‐derived population indices: a case study of emperor penguins. Issue 2 (11th August 2021) - Labrousse, Sara; Iles, David; Viollat, Lise; Fretwell, Peter; Trathan, Philip N.; Zitterbart, Daniel P.; Jenouvrier, Stephanie; LaRue, Michelle
Abstract: Very high‐resolution satellite (VHR) imagery is a promising tool for estimating the abundance of wildlife populations, especially in remote regions where traditional surveys are limited by logistical challenges. Emperor penguins Aptenodytes forsteri were the first species to have a circumpolar population estimate derived via VHR imagery. Here we address an untested assumption from Fretwell et al. (2012) that a single image of an emperor penguin colony is a reasonable representation of the colony for the year the image was taken. We evaluated satellite‐related and environmental variables that might influence the calculated area of penguin pixels to reduce uncertainties in satellite‐based estimates of emperor penguin populations in the future. We focused our analysis on multiple VHR images from three representative colonies: Atka Bay, Stancomb‐Wills (Weddell Sea sector) and Coulman Island (Ross Sea sector) between September and December during 2011. We replicated methods in Fretwell et al. (2012), which included using supervised classification tools in ArcGIS 10.7 software to calculate area occupied by penguins (hereafter referred to as 'population indices') in each image. We found that population indices varied from 2 to nearly 6‐fold, suggesting that penguin pixel areas calculated from a single image may not provide a complete understanding of colony size for that year. Thus, we further highlight the important roles of: (i) sun azimuth and elevation through image resolution and (ii) penguin patchiness (aggregated vs. distributed) on the calculated areas. We found an effect of wind and temperature on penguin patchiness. Despite intra‐seasonal variability in population indices, simulations indicate that reliable, robust population trends are possible by including satellite‐related and environmental covariates and aggregating indices across time and space. Our work provides additional parameters that should be included in future models of population size for emperor penguins. Abstract : Most emperor penguin breeding colonies are projected to be quasi‐extinct by 2100 under 'business as usual' emissions scenarios and thus it is now critical to gain empirical evidence of population changes. Very high‐resolution satellite images (VHR) provide us unprecedented, remote access to monitor emperor penguin populations. Our study is the first to address the cause of uncertainties in emperor penguin population estimates derived via VHR, and to account for uncertainty to optimize population estimates. We found that (i) the assumption within Fretwell et al. (2012) that a single VHR image of an emperor penguin colony is a reasonable representation of the colony size for that year was violated, and that (ii) environmental and satellite‐related covariates helped determine population indices, in an effort toward realistic population estimates. This work has major implications for the future assessment of emperor penguin responses to climate change.